Heuristic Based Planning Approach For Improving Wireless Network Coverage Of Multi-Storey Building - Yeong, Shoa Yei (2011)
This thesis evaluates Wireless Local Area Network (WLAN), in terms of coverage, data rate, and overlapping co-channel interference. The aim of this research is to improve the WLAN coverage by implementing a wireless network planning simulation in multi-storey building. The work presented in this thesis was conducted on both on-site measurement and simulation. A modified theoretical path loss model was presented to estimate the path loss between the transmitter and receiver in the simulation. The results of empirical model were compared with the results of theoretical model and display them in the form of contour visualization.